Seismic performance analysis of building structures using high damping rubber bearings - Anggara, Veron Bella; Rosidawani, Rosidawani; Hanafiah, Hanafiah; Nurjannah, Siti Aisyah; Setiawan, Andri (Gema Wiralodra, 2024)
The problem in this study is how the performance of building structures that have horizontal irregularities using fixed base structures and High Damping Rubber Bearing (HDRB) basic isolated structures. As well as how the performance of building structures compares with horizontal irregularities using HDRB compared to fixed base structures. The purpose of the study was to analyze the effect of the performance of reinforced concrete building structures with horizontal irregularities using fixed base structures and HDRB type basic isolation structures, as well as analyze the comparison of structural performance responses when seismic forces occur on a fixed base and base isolation structures using HDRB in terms of natural periods, shape modes, mass participation, basic shear forces (base shear), story drift, horizontal irregularity, and the influence of the p-delta. This research method is to carry out equivalent static analysis at the initial stage of analysis to obtain minimum force values ​​in the dynamic analysis of the response spectrum in accordance with the provisions of SNI 1726:2019 with the help of Etabs software version V.19. After obtaining the force in the response spectrum analysis results, proceed with designing the structural element reinforcement. Then final stage analysis with non-linear time history analysis (NLTHA) to assess the performance of the building structure. The dynamic analysis of the spectrum response uses spectrum response data for the city of Bengkulu taken from RSA 2021. Meanwhile, the NLTHA analysis uses 7 pairs of horizontal acceleration components selected and matched from individual recordings of MCER ground motion events.The results of this study show that the performance of building structures that have horizontal irregularities with HDRB has better performance than fixed base structures. Comparison of the structure's performance response during seismic forces from several parameters such as natural period, mode shapes, mass participation, base shear, story drift, horizontal irregularity, and p-delta influence. Based on the parameters of the performance of the structure, it proves that the performance of building structures with HDRB has better performance than fixed base. Based on the results of research HDRB can improve the performance of structures that have horizontal irregularities.